Finished dosage form technology электронный курс - Чернова, А. П. химик доцент Томского политехнического университета, кандидат химических наук 1984- (TPU Moodle, 2020)
The goals of adopting the online course and discipline are to form a certain composition of competencies for students (clause 5. General characteristics of main educational program) to prepare for professional activities in the field of analysis and control of the pharmaceutical, chemical, and biotechnological industries. The course "Technology of finished dosage forms" is studied by 1st-year students of the main educational program for the preparation of masters in the specialty 18.04.01 "Chemical technology" in the 1st semester.